2009
DOI: 10.1016/j.neubiorev.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Persistent cognitive dysfunction after traumatic brain injury: A dopamine hypothesis

Abstract: Traumatic brain injury (TBI) represents a significant cause of death and disability in industrialized countries. Of particular importance to patients the chronic effect that TBI has on cognitive function. Therapeutic strategies have been difficult to evaluate because of the complexity of injuries and variety of patient presentations within a TBI population. However, pharmacotherapies targeting dopamine (DA) have consistently shown benefits in attention, behavioral outcome, executive function, and memory. Still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
194
0
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(211 citation statements)
references
References 409 publications
(483 reference statements)
5
194
0
12
Order By: Relevance
“…[15][16][17] Buspirone has been reported to increase dopamine (DA) levels in regions considered essential for cognitive processing such as the prefrontal cortex and hippocampus. 15,48 In addition, numerous studies have shown that DA neurotransmission is important for spatial learning and memory (for excellent reviews, see [10][11][12][13] ). Another potential mechanism may be neuroprotection or restoration of the cholinergic system as evidenced by data showing that 8-OH-DPAT reduced the TBI-induced loss of choline acetyltransferase-positive medial septal cells, which correlated with improved cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Buspirone has been reported to increase dopamine (DA) levels in regions considered essential for cognitive processing such as the prefrontal cortex and hippocampus. 15,48 In addition, numerous studies have shown that DA neurotransmission is important for spatial learning and memory (for excellent reviews, see [10][11][12][13] ). Another potential mechanism may be neuroprotection or restoration of the cholinergic system as evidenced by data showing that 8-OH-DPAT reduced the TBI-induced loss of choline acetyltransferase-positive medial septal cells, which correlated with improved cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial learning consisted on providing four blocks of daily trials (four min intertrial interval) for 5 consecutive days (post-operative days [11][12][13][14][15] in which the rat was given a maximum of 120 sec to find the submerged platform (2 cm below the water surface (i.e., invisible to the rat). On post-operative day 16, the platform was raised 2 cm above the water surface (i.e., visible to the rat) as a control to determine the contributions of nonspatial factors (e.g., sensorimotor performance, motivation, and visual acuity) on cognitive performance.…”
Section: Experiments 1: Buspirone Dose Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Several treatment approaches have been implemented after experimental TBI, leading to numerous pre-clinical studies demonstrating improvement in behavioral and histological outcome (Bales et al, 2009;Garcia et al, 2011;Kokiko and Hamm, 2007;McIntosh et al, 1998;Wheaton et al, 2009). While many of these interventions have produced benefits in the laboratory, the same cannot be said for the clinic (Doppenberg et al, 2004;Menon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) lesioning in mice caused associative memory impairments with depletion of dopamine throughout the brain (Vucković et al 2008). Dopaminergic therapies after TBI illustrate the importance of dopamine for cognitive function/dysfunction after TBI (Bales et al 2009). Our behavioral tests clearly indicated that hypoxic ischemia induces incapacitation of animals' performance and spatial working memory, which were significantly improved by hypothermia treatment.…”
Section: Discussionmentioning
confidence: 99%